Analisa Sistem E-Learning di SMK Menggunakan Metode DeLone and McLean dan UTAUT - Hilqi Kholifatulloh; Titin Kristiana (JURNAL TEKNIK KOMPUTER AMIK BSI, 2024)
Researchers conducted an analysis of the E-Learning system at SMK Muhammadiyah Cimanggu using the Delone & McLean and Utaut methods. In measuring the service quality of the E-Learning system using the Delone & McLean and Utaut method, it has three independent variables including, Performance expectancy (PE), information quality (IQ) and service Quality(SVQ), with the dependent variable being user satisfaction. The analysis technique used is multiple regression with calculation tools using SPSS software. Based on the analysis that has been carried out, there is a positive and significant influence between Performance Expectancy (X1) and Behavioral Intention (X), accepted. The results of the analysis show that there is a significant positive relationship between Performance Expectancy (X1) and Behavioral Intention (X), with a path coefficient of 0.339, t-statistic of 2.264, and p-value of 0.024 and information quality has a significant effect on user satisfaction and satisfaction. user is directly proportional to customer loyalty, while the service quality variable does not have a significant influence on user satisfaction. However, simultaneously, all independent variables have a significant effect on the dependent variable. It is hoped that the website will continue to have good quality.